INVESTIGATION OF THE EFFECTS OF THE ATTITUDES OF PARENTS OF CHILDREN WİTH CANCER TOWARDS PROTECTING THEIR CHILDREN FROM COVID-19 ON THEIR QUALITY OF LIFE AND THEIR CHILDREN'S QUALITY OF LIFE: PROTECTING THEIR CHILDREN FROM COVID-19 - AKDENİZ KUDUBEŞ, ASLI; GÜLCİN; BUSRA; MURAT (Göbeklitepe Medical Science Journal, 2024)
This study was conducted as a descriptive, correlational and cross-sectional study in order to examine the effects of the attitudes of parents who have children with cancer to protect their children from COVID-19 on their quality of life and their children's quality of life. This study was conducted with 160 children aged 7-18 years and their parents, who were treated in the pediatric oncology-hematology clinic of a university hospital. In the collection of research data; Sociodemographic Information Form, Parents' Attitudes Towards Protecting Their Children from COVID-19 Scale (PAS-CV19S), WHOQOL-BREF(TR) World Health Organization Quality of Life Scale Turkish National Short Version, KINDL Scale Oncology Module were used. In the analysis of the research data, mean, percentage calculations and correlation analysis were used. The PAS-CV19S total score average of the children and parents participating in the study, general health, mental health and preventive behaviors sub-dimension score averages were 104,16 + 12,32, 34,00 + 6,08, 22,60 + 2,60 ve 47,56 + 5,87, respectively. WHOQOL-BREF physical well-being, mental (mental) well-being, social relations and environment sub-dimension mean scores were 20,22 + 2,48, 17,21 + 1,81, 7,38 + 1,47 ve 25,82 + 2,95 respectively, and the total mean score of the KINDL Scale, physical, mental, social and treatment sub-dimension mean score was 12,95 + 2,63, 16,51 + 2,71, 11,32 + 5,71, 29,26 + 4,79 ve 69,89 + 8,75 respectively. No correlation was found between PAS-CV19S total score and quality of life sub-dimensions (p>0,05). This study is a study that shows that parents of children with cancer have a very high attitude towards protecting their children from COVID-19, and that their own quality of life and their children's quality of life are quite low.